Single-Dose Ketamine Associated with Rapid Improvement of Depressive Symptoms - Nierengarten, Mary Beth (MD Conference Express, 2014)
Data from a randomized clinical trial show that patients with moderate to severe depressive symptoms treated with a single dose of ketamine show rapid improvement of depressive symptoms compared to patients treated with a psychoactive placebo control. This article discusses outcomes of the Antidepressant Efficacy of Ketamine in Treatment-Resistant Major Depression: A Two-Site Randomized Controlled Trial [Murrough JA et al. Am J Psychiatry 2013].